From the city lens toward urbanisation as a way of seeing: Country/city binaries on an urbanising planet. (January 2017) - Angelo, Hillary
In recent years, three superficially distinct urban subfields have made parallel efforts to incorporate the city's traditional 'outsides' into urban research. Urban political ecology, American urban sociology and postcolonial urban studies have made, respectively, 'nature', the 'rural' and the 'not-yet' city the objects of self-consciously urban analyses. I argue that these interventions are analogous efforts to hybridise city/nature, city/country or society/nature binaries, and that they have a common cause. Each is a response to a persistent 'city lens' that remains pervasive in urban practice, and whose assumptions are an increasingly poor fit for contemporary urban environments. This lens, ground in the context of the 19th century metropolis, interprets the world through a series of binary associations hung on the basic assumption that the city can be defined against a non-urban outside. I develop John Berger's (2008 [1972]) idea of 'ways of seeing' as a heuristic for understanding this situation and, using the case of nature, show how the city lens encourages practitioners and some scholars to romanticise, anachronise or generalise when confronting signs of the not-city in the urban. I conclude by evaluating the limitations of hybridity as a solution to the problems of the city lens, and by outlining an alternative approach. I advocate for turning this way of seeing into a research object, and argue for the importance of an historical and process-oriented examination of the ongoing use of these categories even as critical urban scholars attempt to move beyond them.